Crystal structure and physical properties of the two stannides EuPdSn2 and YbPdSn2. (15th November 2018) - Čurlík, I; Giovannini, M; Gastaldo, F; Strydom, A M; Reiffers, M; Sereni, J G
Abstract: We report on synthesis, crystal structure and physical properties of the isotypic compounds YbPdSn2 and EuPdSn2 crystallizing in the MgCuAl2 -type structure. In both stannides a divalent state of respective rare earth element was found from analysis of the magnetic susceptibilities. Whereas in YbPdSn2 only weak paramagnetic behaviour is observed, in EuPdSn2 a long-range magnetic phase transition occurs at 12.5 K with complex magnetic behaviour evidenced by magnetic susceptibity and specific heat measurements. Under the influence of magnetic field, the magnetic behaviour was found to evolve from an antiferromagnetic to a ferromagnetic state as a consequence of a re-arrangement of magnetic moments.